Diet- and microbiota-related metabolite, 5-aminovaleric acid betaine (5-AVAB), in health and disease - Haikonen Retu; Kärkkäinen Olli; Koistinen Ville; Hanhineva Kati (Elsevier Inc., 2025)
5-Aminovaleric acid betaine (5-AVAB) is a trimethylated compound associated with the gut microbiota, potentially produced endogenously, and related to the dietary intake of certain foods such as whole grains. 5-AVAB accumulates within the metabolically active tissues and has been typically found in higher concentrations in the heart, muscle, and brown adipose tissue. Furthermore, 5-AVAB has been associated with positive health effects such as fetal brain development, insulin secretion, and reduced cancer risk. However, it also has been linked with some negative health outcomes such as cardiovascular disease and fatty liver disease. At the cellular level, 5-AVAB can influence cellular energy metabolism by reducing β-oxidation of fatty acids. This review will focus on the metabolic role of 5-AVAB with respect to both physiology and pathology. Moreover, the analytics and origin of 5-AVAB and related compounds will be reviewed. © 2022 The Authors
Author keywords
5-aminovaleric acid betaine (5-AVAB); aminovaleric acid betaine; N,N,N-trimethyl-5-aminovalerate (TMAV); N,N,N-trimethyl-5-aminovaleric acid (TMAVA); δ-valerobetaine (δVB)